Financial Regulation: Lessons from the Recent Financial Crises - Hoshi, Takeo (Journal of Economic Literature, 2011)
The experiences of the financial crises in the United States recently and in Japan in the 1990s suggest two lessons for future financial regulations. First, the lack of an orderly resolution mechanism for large and complex financial institutions created serious problems. Second, it is important to distinguish between individual financial institutions' health and stability of the whole financial system. Policy recommendations in the Squam Lake Report address these issues well. The Dodd–Frank Act could provide an effective regulatory framework to implement these recommendations, but the success depends on the details of the regulations that have not been specified. (JEL E44, E52, G01, G21, G28, L51)